Detection of pathogens associated with acute febrile illness in children under five years of age in rural Tanzania - Athanasia Maro; AbdulHamid S. Lukambagire; Blandina T. Mmbaga; Jie Liu; Sixbert I. Mkumbaye; Nelson Amani; Judith Njau; Reginald A. Kavishe; Jean Gratz; Eric R. Houpt; Jo E. B. Halliday (Scientific Reports)
Abstract Acute febrile illness (AFI) investigations are crucial for public health. They can provide data on disease prevalence, morbidity, and mortality, and improve treatment, management, control, and detection of outbreaks in areas with limited diagnostic tests. Current understanding of multiple causes of AFI in the paediatric population in Tanzania is limited. This study aimed to simultaneously detect 33 pathogens using TaqMan Array Card based real-time PCR. Whole blood samples were collected from a total of 247 children (2–59 months old) who presented with febrile illness at Dareda and Haydom hospitals in north-eastern Tanzania between November 2015 and March 2016. Overall, 50 (20.2%) and 8 (3.2%) of 247 children had at least one and more than one pathogen detected respectively. Bacterial zoonoses were frequently detected including Brucella spp. (n = 18, 7.3%), C. burnetii (n = 4, 1.6%), Bartonella spp. (n = 3, 1.2%), Rickettsia spp. (n = 3, 1.2%) and Leptospira spp. (n = 1, 0.4%). Dengue virus was detected in 14 (5.7%) individuals and Plasmodium spp. in 12 (4.9%) individuals. These findings reveal the potential clinical importance of zoonoses and arboviruses in febrile children in Tanzania and highlight the need to consider a broad range of pathogens in febrile illness diagnosis.